BUDIDAYA IKAN LELE DUMBO (Clarias gariepinus) DAN IKAN NILA HITAM (Oreochromis niloticus) DALAM EMBER (BUDIKDAMBER) - Deby Setyani; Yusanti Mantuh; Tania Serezova Augusta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The capacity of the environment is one of the factors which needs to be given attention to in aquaculture. With the help of technology and even little media be an increase in the capacity of the environment to catfishes (Clarias gariepinus), black Nile tilapia’s (Oreochromis niloticus), and vegetables in a bucket. The system of the aquaculture of fish in the bucket uses a simple concept and needn't massive capital because needn't no room or ponds. The purpose of this activity is to find the growth of catfishes, black Nile tilapia’s as well as vegetables in the limited area with techniques aquaculture in a bucket, so that can be applied with tiny scales in the household. This activity was carried out in two months from November 2020 up to December 2020 in Palangka Raya. The method is; a. The preparatory stage of vegetable media b. The preparatory stage of media the aquaculture of fish c. Data analysis. Based on the evaluation and monitoring growth catfishes revealed the presence of absolute 15,21 cm long growth and heavy growth is 87,94 gr. The success rate of life as long as maintenance shows the range 66,66 %. While for black nila tilapia’s long growth absolute 6,07 cm and heavy growth is 13,66 gr. The success rate of living in tilapia for maintenance shows a value of 46,66 %. Kale planted in aquaculture containers for 2 months can be harvested as much as 2 times. The results of water quality temperature, pH, and dissolved oxygen (DO) both at the beginning and at the end of the study showed a range of catfishes and tilapias that could still tolerate growth.